Non-Subject Sentences and Subject Sentences Without a Grammatical Subject: A Comparative Study in Slovak, Polish and Croatian - Tibenská, Eva (Slavic Languages Today: Categories, Structures and Processes, 2021)
This study is based on a complex formal-semantic approach to syntax, as opposed to the traditional constituent approach. From the point of view of terminology, this approach distinguishes the grammatical subject, called podmet in Slovak, and the semantic subject with its active (agent) and inactive (bearer) specifications. The comparative analysis presented in this article considers the following three types of Slovak, Polish and Croatian sentence structures: (1) sentences without a grammatical subject and without a subject that represents various atmospheric processes and states; (2) non-subject sentences with a grammatical subject where the subject meaning is included in the obligatory locus participant; (3) sentence structures without a grammatical subject which may include a subject that represents a state of the environment or a physical or mental state of a living organism. The analysis is based on identical reality segments (denotative situations) and on the comparison of all their possible formal and semantic variations (language situations). This approach enables us to better capture syntactic similarities and differences between the languages compared, and the results of such analysis can be used in foreign language teaching.